Analisis Penerapan Kode Etik Penagihan pada Fintech P2p Lending dalam Perspektif Perlindungan Konsumen (Studi Kasus Layanan Pinjaman Online Adakami) - Amoury Adi Sudiro; Aris Machmud; Feby Nurhisyam (Syntax Idea)
The emergence of online loan applications provides a new practical and unsecured option in accounts receivable agreements, allowing many people to use this service. However, the thing that stands out in online loans is related to the behavior of collection officers from fintech P2P Lending companies by not applying ethics and consumer protection principles such as billing cases on the AdaKami application that commit terror, intimidation and threats so that they are detrimental to consumers as users of the application. The purpose of this study is to determine the application of a billing code of ethics that guarantees legal certainty in fintech P2P Lending and legal protection for victims who experience losses for the occurrence of the collection in question. This research uses normative juridical law research methods with a statutory approach (statute approach), analytical approach (analytical approach), and case approach (case approach). The main data collection is carried out by looking at several literatures, undergraduate scientific papers, and laws and regulations to obtain secondary data. The results showed that the application of the billing code of ethics in fintech P2P Lending is still not optimal due to the lack of legal regulations that can adequately protect consumers from actions taken by fintech P2P Lending. Better regulation and legal coordination between relevant parties are needed to enforce the law and protect consumer rights from violations committed by fintech P2P lending companies.